2021
DOI: 10.1097/mlr.0000000000001598
|View full text |Cite
|
Sign up to set email alerts
|

Will Improvements in Patient Experience With Care Impact Clinical and Quality of Care Outcomes?

Abstract: Background: Patient experiences with health care have been widely used as benchmark indicators of quality for providers, health care practices, and health plans.Objective: The objective of this study was to summarize the literature regarding the associations between Consumer Assessment of Healthcare Providers and Systems (CAHPS) patient experiences and clinical and quality outcomes.Research Design: A systematic review of the literature was completed using PubMed, Embase, and Cumulative Index to Nursing and All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In addition to demonstrating disparities in youth and families’ experience of system-of-care principles by level of youth need, findings of this study indicated that youth experienced more improvement in their caregiver-reported well-being when their services were more aligned with system-of-care principles. This finding is consistent with other studies which showed that patient ratings of their care experiences predict the clinical safety and effectiveness of care (Doyle et al, 2013 ; Navarro et al, 2021 ). It also adds to research showing that when families experience care that is more aligned with system-of-care principles, youths experience better clinical outcomes (Hernandez et al, 2001 ; Stephens et al, 2004 ; Williams et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to demonstrating disparities in youth and families’ experience of system-of-care principles by level of youth need, findings of this study indicated that youth experienced more improvement in their caregiver-reported well-being when their services were more aligned with system-of-care principles. This finding is consistent with other studies which showed that patient ratings of their care experiences predict the clinical safety and effectiveness of care (Doyle et al, 2013 ; Navarro et al, 2021 ). It also adds to research showing that when families experience care that is more aligned with system-of-care principles, youths experience better clinical outcomes (Hernandez et al, 2001 ; Stephens et al, 2004 ; Williams et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This concern is mitigated by the explicit centering of family perspectives within systems-of-care (Stroul et al, 2010 ), including in evaluation activities, and by the emphasis on patient-centeredness in healthcare quality frameworks (Co et al, 2011 ). In addition, there is evidence that patient-reported experiences of care predict healthcare safety and clinical effectiveness (Doyle et al, 2013 ; Navarro et al, 2021 ). Nonetheless, future research should incorporate additional measures of adherence to system-of-care principles to substantiate and extend the findings presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The most important PCC factor for schizophrenia relates to information, education, and communication. A recent systematic review showed patient–provider communication to be significantly associated with self-reported physical and mental health (Navarro et al, 2021). Pestana-Santos et al (2018) found that patients with schizophrenia consider clinical communication necessary when assessing psychiatrists' communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…PROMs are important for patients with schizophrenia because pharmacologic interventions should be combined with evidence-based nonpharmacologic treatments and patient-reported outcomes should be employed (Correll, 2020). Finally, a systematic review study also highlighted that higher satisfaction may ultimately improve long-term, simple objective outcomes in patients (Navarro et al, 2021). Thus, based on the above, satisfaction was considered a final patient outcome in this study.…”
Section: Methodsmentioning
confidence: 99%
“…There is data suggesting that improved patient experience with medical care will improve clinical outcomes. 23 However, studies evaluating routine medical care have struggled to characterize effective outcome measures that will determine patient satisfaction. 24 With specific regards to ISBCS, we have identified certain patient circumstances that will affect patient attitudes and their economic burden.…”
Section: Discussionmentioning
confidence: 99%